CRM redefining customer relationship management - Peel, Jeffrey (Amsterdam ; Boston : Digital Press, 2002)
In CRM, Jeffrey Peel defines Customer Relationship Management in a radical new way by putting communications at the center. In the past, CRM was mostly about the technology, not about the customer. In this book, Peel talks about a new ethos that is beginning to fundamentally change the way organizations do business. At a technology level, CRM is increasingly about conjoined best-of-breed applications delivered via portal technologies. At a business level, it is beginning to invade traditional territories occupied by brand management or customer support. Peel shows companies how to make the shift to the new paradigm. Defines the nature of new CRM niche solutions Provides entirely new types of functionality that mesh seamlessly Describes solutions focused solely on the needs of the customer.
The New Customer Challenge; CRM Technology and CRM: The Need for a Communication-Centric Approach; The Analyst's View of CRM; The Application Revolution and Its Implications for CRM; Analytical CRM; Dot-Com CRM Red Herrings and Introducing CMR (and DCM); A Role for Marketing-Oriented CRM Technologies; Selecting Vendor Solutions; Defining CRM Processes; A Researched Approach to CRM; Conclusion; Glossary; Vendor Directory; About the Author; Index.
Includes bibliographical references (p. 187-200) and index.
Keywords: Customer relations -- Management; Electronic books